Dari A-Politis menjadi Ekklesia Politis: Rekonstruksi Pendidikan Kristiani melalui Konsep “Gereja dan Reformasi” Eka Darmaputera - Listia Wangania, Judith Debora (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. This article examines the church's identity crisis in Indonesia, manifested in its apolitical stance. This problem stems from the legacy of theological dualism that separates the spiritual and secular realms, reinforced by a model of Christian education that emphasizes solely individualistic salvation. This paper attempts to reconstruct Christian education to transform it into a political ecclesia, a church with responsible prophetic awareness and involvement in the nation's public and political affairs. This study employs a literature review method, incorporating Eka Darmaputera's key concept of